Катакомбные захоронения главного Верхне-Салтовского могильника (раскопки 1984 года) - Хоружая, М.В. (Степи Европы в эпоху средневековья, 2009)
The paper presents the finds of 24 funeral complexes explored in 1984 by an expedition of the Kharkov Historical Museum in the main catacomb burial ground near Verkhniy Saltov village of Volchansk region of Kharkov province. The explored funeral complexes of such an eponymous monument as Verkhniy Saltov well illustrate the material culture of the Alanian component of the Saltov archaeological culture, their ethno-cultural relations with other East European peoples. Some things found in catacombs 14 and 15 and characteristic of Finno-Ugric peoples of the Middle Volga reaches (the Mordva. Meria, Muroma) are of special interest. The funeral inventory presented in the explored burials permits to specify the dating of this site of the Verkhniy Saltov I (main) catacomb burial ground which enables one to continue developing internal chronology of the Saltov archaeological culture. The explored funeral complexes in most cases may be dated back to the mid - the 2nd half of the 9th century by their inventory and the Arabian silver coins.